(untitled) (The Review of Diabetic Studies, 2025)
Quality management is a pivotal driver of improved patient outcomes, safety, efficiency, and equity in modern health systems. This review comprehensively explores the role of quality in healthcare management by analyzing current trends, challenges, and opportunities. The evolution of quality management from traditional quality assurance to continuous quality improvement, combined with digital health technologies and data-driven approaches, has transformed it into a dynamic, real-time, and patient-centered discipline. Theoretical foundations such as Donabedian’s structure-process-outcome model, Total Quality Management, and Lean Six Sigma provide frameworks for assessing and enhancing quality. The dimensions of quality clinical effectiveness, patient safety, efficiency, equity, timeliness, and patient- centeredness form the basis for evaluating healthcare delivery. Historical milestones, including the emergence of systematic quality measurement and the adoption of continuous quality improvement, have shaped the field. Current trends encompass digital transformation, accreditation, value-based care, patient engagement, and interprofessional collaboration. Quality measurement employs diverse indicators and performance frameworks to monitor and benchmark care delivery. However, challenges persist, including resource constraints, data fragmentation, resistance to change, workforce burnout, and global inequities. Future opportunities lie in integrating artificial intelligence, expanding community-based quality systems, embedding sustainability metrics, enhancing leadership development, and promoting transparency through public reporting. Embracing a holistic, adaptive, and inclusive approach to quality is essential to meet the evolving demands of health systems worldwide and ensure that improvements translate to better health for all populations.